An Analysis of the Concept of Water in Secondary School Biology Textbooks - Musa Dikmenli; Vedat Kadir Ozkan; Selda Kilic; Osman Cardak (Journal of Education in Science, Environment and Health)
As a result of human beings' activities to dominate nature and transform it for their own benefit as they continue to advance in science and technology, environmental problems such as climate change have become the biggest threat faced by the biosphere in the current century. One of the biggest problems of humanity today is the scarcity of water resources. It is important to reveal the meanings attributed to the concept of water in biology textbooks in order to identify and eliminate the deficiencies or gaps between the concepts related to the subject. The main purpose of this study is to analyze how the concept of water is presented in secondary school biology textbooks. In line with this purpose, answers to the following questions were sought: What biological concepts is water associated with in biology textbooks and how often is it used? Under which categories can the concept of water be classified in biology textbooks? In the study, document analysis was conducted on four biology textbooks published by the Ministry of National Education to be taught in high schools in the 2023-2024 academic year. A qualitative methodology based on inductive logic was used to analyze the data. How water is emphasized in biology textbooks was discussed, and categories were developed to conceptualize explanations about water. These categories were: water as a substance in the structure of organisms, water as a habitat for organisms, water as a substance involved in chemical reactions, water as a human health factor, water as an essential requirement for organisms, water as an environmental problem factor and water as a scarcity factor. According to the results of the textbook content analysis, it was seen that the relationships between water and health concepts in the category of water as a human health factor were well structured. In the study, it was seen that the concept of water was presented in accordance with the target achievements in line with the secondary school biology course curriculum and that the key concepts were given literally. However, it was revealed that the concept of water in textbooks should be structured according to the principles of the systems thinking approach.